Increasing students’ higher order thinking skills in science learning through discovery learning assisted by e-worksheet based on Google Docs - Wibowo, Widodo Setiyo; Wasana, Megeng Anung; Muhammad, Fikri Nur (Jurnal Inovasi Pendidikan IPA, 2022)
This study aims to determine the optimal application of discovery learning assisted by an Electronic Worksheet based on Google Docs and to determine the improvement of HOTS of students in Junior High School Students. This research was classroom action research (CAR) with a spiral design by Kemmis and MC Taggart, including the stages of Planning, Implementation, Observation, and Reflection. Learning was carried out in two cycles, each consisting of two meetings. The research subjects were 32 students in the academic year 2021/2022. Data were collected using an instrument of learning implementation observation and test. Data were analyzed descriptively (quantitatively and qualitatively), and inferential statistics to determine the achievement of success indicators. The results show that implementing the discovery learning model has reached the excellent category in cycle II. The results prove that s 78% of students have reached the minimum completeness criteria for HOTs. In addition, there is a significant difference in the average pre-test and post-test scores in the medium category in cycle II. Therefore, it can be concluded that this media can improve students’ HOT.